Ответ:
(1;3) (0.6;4.2)
(1;1) (-1;1) (1;-1) (-1;-1)
(0;-6) (4;-2)
Объяснение:
!!!!!!!!!
Решите систему:
![\frac{2}{y-1} +\frac{3}{x+1} =\frac{5}{2} \\\frac{1}{x-2} =-\frac{3}{y} \\\\ODZ:\\(y-1)(x+1)\neq 0\\y\neq 1;x\neq -1\\y(x-2)\neq 0\\y\neq 0\\x-2\neq 0\\x\neq 2\\\frac{2}{y-1} +\frac{3}{x+1} =\frac{5}{2}\\y=-3(x-2)\\\\\frac{2}{y-1} +\frac{3}{x+1} =\frac{5}{2}\\y=-3x+6 \frac{2}{y-1} +\frac{3}{x+1} =\frac{5}{2} \\\frac{1}{x-2} =-\frac{3}{y} \\\\ODZ:\\(y-1)(x+1)\neq 0\\y\neq 1;x\neq -1\\y(x-2)\neq 0\\y\neq 0\\x-2\neq 0\\x\neq 2\\\frac{2}{y-1} +\frac{3}{x+1} =\frac{5}{2}\\y=-3(x-2)\\\\\frac{2}{y-1} +\frac{3}{x+1} =\frac{5}{2}\\y=-3x+6](https://tex.z-dn.net/?f=%5Cfrac%7B2%7D%7By-1%7D%20%2B%5Cfrac%7B3%7D%7Bx%2B1%7D%20%3D%5Cfrac%7B5%7D%7B2%7D%20%5C%5C%5Cfrac%7B1%7D%7Bx-2%7D%20%3D-%5Cfrac%7B3%7D%7By%7D%20%5C%5C%5C%5CODZ%3A%5C%5C%28y-1%29%28x%2B1%29%5Cneq%200%5C%5Cy%5Cneq%201%3Bx%5Cneq%20-1%5C%5Cy%28x-2%29%5Cneq%200%5C%5Cy%5Cneq%200%5C%5Cx-2%5Cneq%200%5C%5Cx%5Cneq%202%5C%5C%5Cfrac%7B2%7D%7By-1%7D%20%2B%5Cfrac%7B3%7D%7Bx%2B1%7D%20%3D%5Cfrac%7B5%7D%7B2%7D%5C%5Cy%3D-3%28x-2%29%5C%5C%5C%5C%5Cfrac%7B2%7D%7By-1%7D%20%2B%5Cfrac%7B3%7D%7Bx%2B1%7D%20%3D%5Cfrac%7B5%7D%7B2%7D%5C%5Cy%3D-3x%2B6)
![\frac{2}{y-1} +\frac{3}{x+1} =\frac{5}{2}\\\\\frac{2}{-3x+6-1}+\frac{3}{x+1} =2.5\\\\\frac{2}{-3x+5} +\frac{3}{x+1} =2.5\\\\2(x+1)+3(-3x+5)=2.5(-3x+5)(x+1) \frac{2}{y-1} +\frac{3}{x+1} =\frac{5}{2}\\\\\frac{2}{-3x+6-1}+\frac{3}{x+1} =2.5\\\\\frac{2}{-3x+5} +\frac{3}{x+1} =2.5\\\\2(x+1)+3(-3x+5)=2.5(-3x+5)(x+1)](https://tex.z-dn.net/?f=%5Cfrac%7B2%7D%7By-1%7D%20%2B%5Cfrac%7B3%7D%7Bx%2B1%7D%20%3D%5Cfrac%7B5%7D%7B2%7D%5C%5C%5C%5C%5Cfrac%7B2%7D%7B-3x%2B6-1%7D%2B%5Cfrac%7B3%7D%7Bx%2B1%7D%20%20%3D2.5%5C%5C%5C%5C%5Cfrac%7B2%7D%7B-3x%2B5%7D%20%2B%5Cfrac%7B3%7D%7Bx%2B1%7D%20%3D2.5%5C%5C%5C%5C2%28x%2B1%29%2B3%28-3x%2B5%29%3D2.5%28-3x%2B5%29%28x%2B1%29)
ODZ:
(x+1)(-3x+5)≠0
x≠-1 ; 1 2/3
![2x+2+(-9x+15)=2.5(-3x+5)(x+1)\\2x+2-9x+15-2.5(-3x+5)(x+1)=0\\-7x+17-2.5(-3x+5)(x+1)=0\\-7x+17-2.5(-3x^2+2x+5)=0\\-7x+17+7.5x^2-5x-12.5=0\\7.5x^2-12x+4.5=0\\75x^2-120x+45=0\\15x^2-24x+9=0\\5x^2-8x+3=0\\D=64-60=4\\\sqrt{4} =2 2x+2+(-9x+15)=2.5(-3x+5)(x+1)\\2x+2-9x+15-2.5(-3x+5)(x+1)=0\\-7x+17-2.5(-3x+5)(x+1)=0\\-7x+17-2.5(-3x^2+2x+5)=0\\-7x+17+7.5x^2-5x-12.5=0\\7.5x^2-12x+4.5=0\\75x^2-120x+45=0\\15x^2-24x+9=0\\5x^2-8x+3=0\\D=64-60=4\\\sqrt{4} =2](https://tex.z-dn.net/?f=2x%2B2%2B%28-9x%2B15%29%3D2.5%28-3x%2B5%29%28x%2B1%29%5C%5C2x%2B2-9x%2B15-2.5%28-3x%2B5%29%28x%2B1%29%3D0%5C%5C-7x%2B17-2.5%28-3x%2B5%29%28x%2B1%29%3D0%5C%5C-7x%2B17-2.5%28-3x%5E2%2B2x%2B5%29%3D0%5C%5C-7x%2B17%2B7.5x%5E2-5x-12.5%3D0%5C%5C7.5x%5E2-12x%2B4.5%3D0%5C%5C75x%5E2-120x%2B45%3D0%5C%5C15x%5E2-24x%2B9%3D0%5C%5C5x%5E2-8x%2B3%3D0%5C%5CD%3D64-60%3D4%5C%5C%5Csqrt%7B4%7D%20%3D2)
x₁=(8+2)/10=1;
x₂=(8-2)/10=6/10=3/5
Подставим:
x₁=1
x₂=3/5 = 0.6
![y=-3x+6\\y=-3*1+6\\y=-3+6\\y=3\\\\y=-3x+6\\y=-3*\frac{3}{5} +6\\\\y=-\frac{9}{5} +6\\\\y=\frac{-9+30}{5} =\frac{21}{5} =4.2 y=-3x+6\\y=-3*1+6\\y=-3+6\\y=3\\\\y=-3x+6\\y=-3*\frac{3}{5} +6\\\\y=-\frac{9}{5} +6\\\\y=\frac{-9+30}{5} =\frac{21}{5} =4.2](https://tex.z-dn.net/?f=y%3D-3x%2B6%5C%5Cy%3D-3%2A1%2B6%5C%5Cy%3D-3%2B6%5C%5Cy%3D3%5C%5C%5C%5Cy%3D-3x%2B6%5C%5Cy%3D-3%2A%5Cfrac%7B3%7D%7B5%7D%20%2B6%5C%5C%5C%5Cy%3D-%5Cfrac%7B9%7D%7B5%7D%20%2B6%5C%5C%5C%5Cy%3D%5Cfrac%7B-9%2B30%7D%7B5%7D%20%3D%5Cfrac%7B21%7D%7B5%7D%20%3D4.2)
⇒⇒⇒⇒⇒⇒⇒⇒⇒⇒
y₁=3
y₂=4.2
Получим ответ:
(1;3) (0.6;4.2)
Вторая система:
3x²-2y²=1 ⇒ 3x²-2y²=1
2x²-y²=1 -4x²+2y²=-2
3x²-2y²-4x²+2y²=1+(-2)
-x²=-1
x²=1
x=±1
x₁=1
x₂=-1
Подставим:
2x²-y²=1
2-y²=1
-y²=-1
y²=1
y=±1
2x²-y²=1
2-y²=1
-y²=-1
y²=1
y=±1
Получим 4 решения:
(1;1) (-1;1) (1;-1) (-1;-1)
Третья система:
3x+y+2xy=-6 ⇒ 3x+y+2xy=-6
x+y+xy=-6 -2x-2y-2xy=12
3x+y+2xy-2x-2y-2xy=-6+12
x-y=6
-x+y=-6
y=-6+x
Подставим:
x+y+xy=-6
x+(-6+x)+x(-6+x)=-6
x-6+x-6x+x²+6=0
x²-4x=0
x(x-4)=0
x=0 или x-4=0
x=4
x₁=0
x₂=4
Подставим:
y=-6+x y=-6+x
y=-6+0 y=-6+4
y=-6 y=-2
y₁=-6
y₂=-2
Запишем решение;
(0;-6) (4;-2)